Slicing the pie: Interpreting harmful algal blooms one pie chart at a time. (18th October 2022) - Richlen, Mindy L.; Curran, Mary Carla; Chadwick, Christina; Hubbard, Katherine A.
Abstract: The Earth's oceans are home to a diverse array of life, from large marine mammals to microscopic organisms. Among the most important are the marine phytoplankton, which comprise the basis of marine food webs, and also produce a large percentage of the Earth's oxygen through photosynthesis. Although the vast majority of phytoplankton are essential to ocean health, several dozen species produce potent toxins, and can form what are called Harmful Algal Blooms (HABs). This science activity focuses on the importance of HABs, as well as the types of data scientists collect to understand blooms. In the classroom exercises, students will calculate the proportional abundance (% contribution) of five HAB species present in water samples, and use these data to create pie graphs to depict species composition. Students will then compare these results with levels of HAB toxins in water samples collected over the same time period. Thought questions challenge students to develop hypotheses regarding how changes in the HAB community may relate to observed trends in toxin concentrations. This activity was successfully taught to visually impaired students who were able to complete the pie charts and answer the thought questions.